Monodentate coordination of the normally chelating chiral diamine (R, R)-TMCDA. Issue 2 (13th December 2016) - Ojeda-Amador, Ana I.; Martínez-Martínez, Antonio J.; Kennedy, Alan. R.; Armstrong, David R.; O'Hara, Charles T.
Abstract : Contrary to previous studies, this work shows that the chiral diamine ( R, R )-TMCDA can bind to a metal in a monodentate manner. Abstract : After isolating an unusual binuclear, but monosolvated NaHMDS complex [{( R, R )-TMCDA}·(NaHMDS)2 ]∞ which polymerises via intermolecular electrostatic Na⋯MeHMDS interactions, further ( R, R )-TMCDA was added to produce the discrete binuclear amide [{κ 2 -( R, R )-TMCDA}·(NaHMDS)2 {κ 1 -( R, R )-TMCDA}], whose salient feature is the unique monodentate coordination of one of the chiral diamine ligands.